2010
DOI: 10.1007/s13187-010-0083-0
|View full text |Cite
|
Sign up to set email alerts
|

“No Respecter of Youth”: Over-representation of Young Women in Australian Television Coverage of Breast Cancer

Abstract: Ninety four percent of new breast cancer cases in Australian women occur in those aged over 40. Mammographic breast screening programs target women over 40, especially those aged 50-69, but participation rates in this age group have recently declined. To test the hypothesis that young women, at low risk for breast cancer, are overrepresented in television news, we analyzed all televised news reports on age and breast cancer shown on five free-to-air Sydney television stations, from 3 May 2005 to 28 February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Consistent with previous research [64], we found that, for each disease type, the media presented both biased and "typical" images of patients and their efforts to cope with hair loss. Importantly, our findings revealed the ways media marginalize each of the studied group.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous research [64], we found that, for each disease type, the media presented both biased and "typical" images of patients and their efforts to cope with hair loss. Importantly, our findings revealed the ways media marginalize each of the studied group.…”
Section: Discussionsupporting
confidence: 89%
“…In the broader population, the media is another factor that shapes understandings of breast cancer causation among women. For example, media coverage of celebrity diagnoses of breast cancer in young women may have led to underestimation of age as a risk factor [27]. Similarly, reports focused on personal accounts of affected women with a family history of breast cancer may have influenced views that breast cancer is a predominantly genetic disease [28].…”
mentioning
confidence: 99%
“…On the other hand, however, breast cancer continues to be quite unique in terms of the media attention it receives, and this may continue to create disproportionate alarm even among young females [2,21,22]. In fact, different studies have found that women under the age of 50 and even 40 are often represented in the mass media as the typical breast cancer patient/survivor [23,24], even though they constitute a minority of those diagnosed with breast cancer [25]. Second, it is important to identify the specific factors that may explain the potential heightened fear of breast cancer among this age group.…”
Section: The Present Studymentioning
confidence: 99%
“…Doing so may help plan for more effective media campaigns or educational interventions wherein any information gaps can be properly addressed early on in women's lives, without creating unnecessary concern about breast cancer. Previous studies have in fact shown that the inaccurate/alarmist representation of breast cancer information can increase doubts among young women as to whether they should also be regularly screened, often putting in question recommendation for mammography screening [24]. In Spain breast cancer screening is based on recommendations from the European Union: all women between the ages of 50 and 69 are eligible for biannual mammograms, whereas women with a family history of breast cancer are also screened between the ages of 45 and 49 [43].…”
Section: Plos Onementioning
confidence: 99%